STRUKTUR ASOSIASI SPESIES TARGET PADA TERUMBU KARANG BUATAN di PERAIRAN SELAT BANGKA, KABUPATEN MINAHASA UTARA - Emil Reppie; Daniel R. Monintja; M. Fedi A. Sondita; Indra Jaya; Victor P.H. Nikijuluw (Buletin PSP, 2006)
Artificial reefs exhibit significant potential as an instrument in rehabilitation of coastal ecosystems or at least as an alternative to decrease the harvesting pressure on natural reefs by creating new fishing grounds. However, their utilization as reef fishing grounds in practice, may not be optimal without significant support of protected nursery ground reefs. This research was done to study the effectiveness of some artificial reef designs as nursery ground of target species. Three types of reinforced concrete block reef designs were chosen and constructed, they were cube, trapezium and combination in shapes; 0.5 m2 in total volume each; and a unit of patch reef used in comparison. The results show that natural reef still dominated the abundance of total individual species observed; but in the term of fish biomass showed that combination design more abundance than natural reef and the other two reef designs. This result indicated that reef designs (which have been constructed), in an optimal circumstance exhibit a significant potential as a nursery ground of coral fishes.